Contributions of postgraduate studies in the training of university professors - Bailey-Moreno, Josefina (IE Revista de Investigación Educativa de la REDIECH, 2021)
Postgraduate studies are relevant because their implications in the training of teachers, particularly in the teaching processes. The purpose of this research was to know what is the contribution of postgraduate studies in the educational practice of professors teaching in university. Focusing on grounded theory an explanatory scheme was created from theoretical sampling, constant comparison, and the categorization of data collected through interviews. Ten Mexican teachers with different backgrounds and areas of knowledge in teaching participated. The results indicate that learning regarding pedagogical theories and strategies as well as practical experiential learning and useful knowledge were valued because they are considered transferable to teaching, while research and deepening in the field of postgraduate knowledge were estimated as learning not related to teaching. These results suggest reflecting on and incorporating in postgraduate studies, teacher learning processes with a broad vision of teaching that addresses the theory and practice of teaching and the field of knowledge of the discipline being taught, as well as research on the practice in order to enhance their formation.